2007
DOI: 10.1196/annals.1395.022
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Paraoxonase Activity Changes in Turkish Population

Abstract: Paraoxonase1 (PON1) is a high-density lipoprotein (HDL)-associated enzyme capable of hydrolyzing diverse substrates from organophosphate (OP) toxins to oxidized phospholipids. As such, it has been linked with both the prevention of OP poisoning and inhibition of atherosclerosis initiated by oxidatively modified low-density lipoprotein (LDL). The aim of this study was to investigate, with aging, the activity of PON1 associated with HDL and partially responsible for its antiatherogenic activity. The study involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…A lack of independent association of age with any measure of PON activity in the current analysis is consistent with a number of other studies 12, 14, 35. In the largest of these ( n =1527), Roest et al reported PON activities of 159, 166 and 151 U/L in subgroups with an age of <53, 53–60 and >60 years, respectively 12.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A lack of independent association of age with any measure of PON activity in the current analysis is consistent with a number of other studies 12, 14, 35. In the largest of these ( n =1527), Roest et al reported PON activities of 159, 166 and 151 U/L in subgroups with an age of <53, 53–60 and >60 years, respectively 12.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, although not shown to be independent predictors of CVD, a number of additional coding and promoter gene variants have been shown to impact PON activity and circulating protein levels 10–12. However, apart from the impact of PON genotypes, determinants of circulating PON‐1 concentration and activity are poorly understood, with associations with age, HDL‐cholesterol (HDL‐C), alcohol and smoking status inconsistently reported in the literature 10, 12–16.…”
Section: Introductionmentioning
confidence: 99%
“…There were no differences in these enzymatic activities when the whole study population was grouped by ages 21-40 years and [41 years (P = 0.760). In agreement, Saruhan et al [34] reported that age did not affect PON1 serum activity levels. In contrast, Seres et al [35], who worked with three groups with age differences of over 20 years, found age-associated differences in the enzymatic activity of PON1.…”
Section: Discussionmentioning
confidence: 58%
“…The decreased activities correlated negatively with oxLDL increase; with the increased oxidation of hydrophobic amino acid residues and hydroxy and hydroperoxy derivatives; and with the increased protein carbonylation and protein oxidation products. However, in the Turkish population, the PON-1 activity was no different between young and old people [201]. A meta-analysis consisting of 5962 subjects, 2795 young (<65 years of age) and 3167 old subjects (>65 years of age), described that subjects carrying RR and QR genotypes (R+ carriers) were favoured in reaching extreme ages, since centenarian and nonagenarian individuals did not have and/or delay the onset of major age-related diseases [202].…”
Section: Paraoxanase In Healthy Old Peoplementioning
confidence: 99%